2023
DOI: 10.21037/qims-22-655
|View full text |Cite
|
Sign up to set email alerts
|

Coronary computed tomography angiography assessment of relationship between right coronary artery-aorta angle and the development of coronary artery disease

Abstract: Whilst a correlation has been established between wide left main coronary artery bifurcation[left anterior descending-left circumflex (LAD-LCx)] angle (>80°) and the development of coronary artery disease (CAD), this retrospective, causal-comparative pilot study aimed to explore whether a relationship exists between right coronary artery (RCA)-aorta angle and CAD. Thirty normal cases were identified via radiology reports and selected as the control group with coronary computed tomography angiography (CCTA) sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The results of this study suggest a relationship between narrow RCA-aorta angles and CAD (Figure 5), supporting the preliminary findings of our recent study [18]. There is currently very little literature available discussing possible relationships between the RCA-aorta angle and CAD.…”
Section: Relationship Between Rca-aorta Angle and Cadsupporting
confidence: 91%
See 4 more Smart Citations
“…The results of this study suggest a relationship between narrow RCA-aorta angles and CAD (Figure 5), supporting the preliminary findings of our recent study [18]. There is currently very little literature available discussing possible relationships between the RCA-aorta angle and CAD.…”
Section: Relationship Between Rca-aorta Angle and Cadsupporting
confidence: 91%
“…If the RCA follows an immediately inferior path, an axial-acquired RCA-aorta measurement will be larger than the true angle size. Consequently, this method generally results in a consistently overestimated RCA-aorta angle (Figure 3), and it was concluded that this angle may be better assessed using MPRs [18]. Hence, the RCA-aorta angle was measured via MPR images in this study, by manipulating obliqued planes to identify and measure the smallest observable RCA-aorta angle.…”
Section: Coronary Angle Measurementmentioning
confidence: 95%
See 3 more Smart Citations